PERANGSANG POSITIF BAGI PETANI PEREMPUAN UNTUK PENERAPAN PUPUK RAMAH LINGKUNGAN DI DAERAH TANGKAPAN AIR DANAU TONDANO - Andry H. Umboh & Euis F.S. Pangemanan (EKOTON, 2012)
An action-research of providing the positive incentive for women farmer in order to apply the environmental friendly fertilizer in Tondano Lake Catchment Area has been conducted in three villages of Tondano Lake intensive areas. The actions were recruitment of women farmer participants, participants training, and the providing of agricultural capital for participants, while the researches were the examination and the study on the effects of the incentive-oriented actions on the women farmer participation in application of organic fertilizer in Tondano lake watershed. The results showed that positive incentive in the form of capital for cropping activities was the main reason that attracted women farmers to participate in environmental conservation endeavors. It was concluded that positive incentive should be considered in any sustainable environmental management effort.